2017
DOI: 10.1371/journal.pone.0180295
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of FTO/IRX region with obesity and overweight in the Polish population

Abstract: Background/ObjectivesGenome-wide association studies (GWAS) have identified many loci associated with body mass index (BMI) in many different populations. Variants in the FTO locus are reported to be one of the strongest genetic predictors of obesity. Recent publications pointed also to a topologically associated domain (TAD) which is identified as a novel region affecting BMI. The TAD area encompasses the IRXB cluster (IRX3, IRX5, IRX6), FTO and RPGRIP1L genes.Subjects/MethodsIn this study, we investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 60 publications
(63 reference statements)
4
49
0
3
Order By: Relevance
“…The outcomes of our study and the one of and Sobalska-Kwapis et al suggest that in Polish women, obesity is less influenced by FTO polymorphism than in men. 26 To further explore this problem, we analyzed the FTO influence on obesity in female subgroups according to menopausal status and age, but it did not change our results. There are suggestions that the association between FTO gene and obesity is age-dependent.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The outcomes of our study and the one of and Sobalska-Kwapis et al suggest that in Polish women, obesity is less influenced by FTO polymorphism than in men. 26 To further explore this problem, we analyzed the FTO influence on obesity in female subgroups according to menopausal status and age, but it did not change our results. There are suggestions that the association between FTO gene and obesity is age-dependent.…”
Section: Discussionmentioning
confidence: 94%
“…It has been also revealed in this study that obesity-associated SNPs had a different inheritance model in men (recessive) than in women (dominant). 26 In the Mexican population, Saldaña-Alvarez et al have shown, in turn, that 2 FTO SNPs were specifically associated in men under a dominant model, while 3 were associated with women under additive and recessive models. 31 Together with our results, this highlights the need to consider sex as an important factor modulating FTO genetic association with overweight and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FTO SNPs were associated with obesity among females only when assuming a dominant inheritance model, whereas among males when assuming a recessive inheritance model. A strong association of FTO intronic variants with overweight was revealed only in men, suggesting that overweight might be regulated by a different genetic manner dependent on sex, and probably controlled by other genomic region(s) in females (Sobalska‐Kwapis et al, ).…”
Section: Discussionmentioning
confidence: 99%